2020
DOI: 10.3389/fpsyt.2020.00855
|View full text |Cite
|
Sign up to set email alerts
|

The Gut Microbiota and Associated Metabolites Are Altered in Sleep Disorder of Children With Autism Spectrum Disorders

Abstract: Background Autism spectrum disorder (ASD) is a type of neurodevelopmental disease that is frequently accompanied by sleep disorder. Herein, we investigated changes in the gut microbiota and its metabolites correlated with core symptoms and sleep problems in children with ASD. Methods One hundred and twenty children diagnosed with ASD based on Diagnostic and Statistical Manual of Mental Disorders (DSM-5) criteria were enrolled in our study. The Autism Behavior Checklist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 49 publications
4
60
0
1
Order By: Relevance
“…There are currently a large number of studies on the overall sleep status and autism symptoms of ASD, so we do not separately analyze and discuss it, but focus the research on different dimensions. For this study, it is the four dimensions of with the highest prevalence [ 44 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are currently a large number of studies on the overall sleep status and autism symptoms of ASD, so we do not separately analyze and discuss it, but focus the research on different dimensions. For this study, it is the four dimensions of with the highest prevalence [ 44 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the gut-brain axis has been widely described and a growing body of evidence highlights a role for alterations in the GM in the pathophysiology of many neurologic and neuropsychiatric diseases, including autism spectrum disorder (ASD). Hua and co-workers reported a significantly reduction in the abundances of butyrate-producing bacteria Faecalibacterium and Agathobacter in ASD children [ 62 ]. To further emphasize this link recent work has shown that GM alterations leads to have a significant impact on amygdala development in infancy, modulating the development of the frontal cortex and other brain regions [ 63 ].…”
Section: Butyratementioning
confidence: 99%
“…In a Chinese population of 120 children with ASD, Hua et al [ 191 ] explored the differences in the composition of the gut microbiome and its metabolites between those patients who suffered from sleep disorders ( n = 60) and those without sleep problems ( n = 60). Sleep disorders were assessed through the Children Sleep Habits Questionnaire (CSHQ).…”
Section: Microbiota–gut–brain Axis and Attention-deficit And/or Hymentioning
confidence: 99%